Carbohydrate refeed does not modify GVT-performance following energy restriction in bodybuilders. (June 2021) - Moura, Ronaldo Ferreira; De Moraes, Wilson Max Almeida Monteiro; De Castro, Bruno Magalhães; Nogueira, André Luiz Pinto; Trindade, Thiago Barbosa; Schoenfeld, Brad J.; Prestes, Jonato
Summary: Bodybuilding is a sport in which competitors' physiques are judged on their muscular size, symmetry, and leanness, as displayed in a number of different poses. In the pre-competitive period, bodybuilders attempt to reduce body fat stores as much as possible while maintaining fat-free mass (FFM). This is achieved via a sustained negative energy balance, generally induced by a combination of decreased energy intake and increased energy expenditure. This study aimed to assess the ability of bodybuilders to resist fatigue during resistance exercise based German Volume Training (GVT), as well as the affective response after carbohydrate refeed following four weeks of moderate or severe energy restriction. Eleven male bodybuilders (28.4 ± 2.3 years old) with experience in competitions were randomized into two groups: Moderate Energy Restriction (MER; n = 6) or Severe Energy Restriction (SER; n = 5). On the 2nd day (during energy restriction) and 7th day (during refeed) of the fourth week, both groups completed two leg press protocols involving the GVT method. After the first and last workout protocol subjects were assessed for muscle soreness using the visual–analog scale (VAS), rating of perceived exertion (RPE), affective response, lactate, and creatine kinase. Anthropometric analysis indicated that a reduction of 3.7 and 3.2% in body mass corresponded to a loss of 16.0 and 17.6% of fat mass for the MER and SER groups, respectively, with both groups maintaining FFM. Blood CK and VAS values were reduced only in SER. Our results suggest that a carbohydrate refeed may help to attenuate the perception of muscle soreness and maintain exercise performance, especially when severe energy restriction is combined with an intense training protocol such as GVT.